The Emergence of Severe Pulmonary Hemorrhagic Leptospirosis: Questions to Consider - Truong, Kim N.; Coburn, Jenifer (Frontiers in Cellular and Infection Microbiology, 2012)
Since the 1980s, the incidence of severe pulmonary hemorrhage caused by Leptospira spp. infection has increased. The mild, non-specific symptoms or the more classical form of severe disease with hepatorenal manifestations, Weil’s syndrome, predominate world-wide. However, several regions of the world have seen increases in numbers of patients with pulmonary hemorrhage attributed to leptospirosis. The reasons behind the emergence of this syndrome, which carries a high mortality rate, are not known. Several avenues for future research may shed light on the mechanisms involved in development of pulmonary hemorrhage, and inform targeted therapeutics to improve outcomes. Possibilities to consider include: 1) emergence of new bacterial strains, 2) acquisition of virulence traits by strains in the endemic regions, 3) changes in underlying health of the affected human populations, and 4) increased recognition of the syndrome and better record keeping by the medical and veterinary communities. Determining the causes of emerging clinical manifestations presents challenges and opportunities for potentially life-saving research into the pathogenesis of a number of infectious diseases, including leptospirosis.